Finding some seagrass optimism in Wales, the case of Zostera noltii - Chiara Bertelli (Marine Pollution Bulletin, 2017)
There exists limited understanding of the long-term dynamics of the seagrass Zostera noltii and how this is influenced by anthropogenic pressures. Milford Haven is a heavily industrialised estuary and also one of the important sites for Zostera sp. in the UK. In this study we examine all available long-term spatial variability and abundance data of Zostera noltii within Milford Haven using historic datasets. Results show that Z. noltii in all sites have shown meadow expansion when compared to the first obtainable records. Little change in abundance over the past 10–15 years for the two sites confirms certain seagrass populations to be robust and thriving. We hypothesise that these populations are showing a level of resilience to the high nutrient levels, disturbance and high turbidity present within the water column of the Haven.